Gene expression analyses of the calmodulin binding protein 60 family under water stress conditions in rice - Bishun Deo Prasad; Ramakant; Sangita Sahni; Diksha Kumari; Pankaj Kumar; Sanjay J. Jambhulkar; Saud Alamri; Muhammad Faheem Adil (Scientific Reports)
Abstract Plants have developed elaborate mechanisms for perceiving extracellular stimuli and subsequently activating defense reactions through a multifaceted interaction of signaling cascades. Calcium ion (Ca²⁺), an essential and ubiquitous intracellular second messenger molecules, whose concentration ([Ca2+]cyt) has been observed to rise in response to numerous environmental stresses. The calcium/calmodulin (Ca²⁺/CaM) complex triggers apposite cellular responses through modifying the activities of a varied array of CaM-binding proteins (CBPs). Among CBPs, the CBP60 gene family has been identified as key regulators of stress responses in several crop species. Recently, we have demonstrated the expanded and diversified role of OsCBP60 in rice against devastating pathogens. Here, we analyzed the diversified roles of OsCBP60s in two major abiotic stresses, namely reproductive drought and submergence stress. OsCBP60bcd-2 and OsCBP60g-1/OsSARD1 were consistently upregulated during reproductive drought stress in rice. However, OsCBP60g-5 and OsCBP60g-6 were steadily up-regulated under submergence stress in rice. Interestingly, OsCBP60g-4 was consistently upregulated in both abiotic stresses, except on the third day of reproductive drought. The differential expression of OsCBP60s under water stress highlights the importance of further studying these genes as potential targets for enhancing stress resilience in rice.